PENGARUH EFEKTIVITAS PENERAPAN SIA, PEMANFAATAN, DAN KESESUAIAN TUGAS TERHADAP KINERJA KARYAWAN - Astuti, Ni Made Marlita Puji; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 9 No 3 (2014), 2014)
Sustainability and success of the organization can be determined from the performance of the employee owned. It is expected that employees are able to complete the task and produce information in a timely, accurate, and reliable. This study was conducted to determine the effect of the effectiveness of the implementation of accounting information systems, information technology utilization and appropriateness of tasks with information technology on employee performance. The research was conducted on Credit Unions in Gianyar regency. Samples were taken by purposive sampling technique 40 Credit Unions. Respondents in this study is the chairman or manager, treasurer and cashier. Using multiple linear regression analysis. The results showed the effectiveness of the implementation of accounting information systems, and the suitability of the use of information technology tasks has a positive and significant influence on employee performance.
Keywords: SIA, technology, and suitability